<h2>
Answer:</h2>
4x - 6 + 2x = 3(2x - 2)
4x - 6 + 2x = 6x - 6
[ both sides - 6 cancel each other ]
4x + 2x = 6x
6x = 6x
[ both sides 6x cancel each other ]
0 = 0.
The solution to the given equation is -87/45
<h3>Product of expressions</h3>
Given the following expression that represents the word problem as;
-1/5 * 3 - 12(1/3)^2
Using the PEMDAS rule, the parenthesis and exponent will come first to have;
-1/5 * 3 - 12(1/3)^2 = -1/5 * 3 - 12(1/9)
Then multiplication
-1/5 * 3 - 12(1/9) =. -3/5 - 12/9
Find the difference
-1/5 * 3 - 12(1/9) = -27-60/45
-1/5 * 3 - 12(1/9) = -87/45
Hence the solution to the given equation is -87/45
Learn more on PEMDAS here; brainly.com/question/345677
#SPJ1
Answer:
76
Step-by-step explanation:
blah blah blah blah blah blah blah
Answer
-8\leq 7x\\
Step-by-step explanation: